2018
DOI: 10.1021/acs.jnatprod.8b00585
|View full text |Cite
|
Sign up to set email alerts
|

Coumarinolignoids and Taraxerane Triterpenoids from Sapium discolor and Their Inhibitory Potential on Microglial Nitric Oxide Production

Abstract: Seventeen compounds, including three new pairs of coumarinolignoid enantiomers, (7′S,8′S)-sapiumins A−C (1a−3a) and (7′R,8′R)sapiumins A−C (1b−3b), six new taraxerane triterpenoids, sapiumic acids A−F (4−9), and five known taraxerane triterpenoids (10−14), were isolated from an ethanol extract prepared from the stems and leaves of Sapium discolor. The structures of 1−9 and their relative configurations were determined by spectroscopic data analysis, and the absolute configurations of the coumarinolignoids 1a/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In turn, the ROE correlations of H 3 -24/H 3 -25, H 3 -25/H-11, H 3 -26/H-11, H 3 -28/H-18, and H 3 -29/H-18 suggested these protons to be β-oriented in 11. Meanwhile, the magnitude of J H-7′/H-8′ (10.4 Hz) indicated a trans configuration of the dioxane ring, 27 and the ROE correlation between H-8′ and H-11 supported their β-orientation. The ROE correlation between H-2′ and the methoxy group also confirmed the latter to be located at C-3′.…”
Section: Resultsmentioning
confidence: 95%
“…In turn, the ROE correlations of H 3 -24/H 3 -25, H 3 -25/H-11, H 3 -26/H-11, H 3 -28/H-18, and H 3 -29/H-18 suggested these protons to be β-oriented in 11. Meanwhile, the magnitude of J H-7′/H-8′ (10.4 Hz) indicated a trans configuration of the dioxane ring, 27 and the ROE correlation between H-8′ and H-11 supported their β-orientation. The ROE correlation between H-2′ and the methoxy group also confirmed the latter to be located at C-3′.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, alkaloids were absent in this extract. Recent studies on the chemistry of T. cochinchinensis have shown the occurrence of terpenoids from the leaf and stem, including diterpenoids and triterpenoids (Liu et al, 2015;Zhang et al, 2018). In addition, coumarinolignoids and lignoids also were reported from the same parts of this plant (Zang et al, 2018;Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, the plant has been reported to contain diterpenoids, phenolics, triterpenoids, coumarinolignoids, and lignoids from leaf and stem parts. Their biological activities include anticancer activity and nitric oxide inhibition in BV-2 microglial cells induced by lipopolysaccharide (Liu et al, 2015;Zhang et al, 2018;Zhang et al, 2019). In this study, the antioxidant and…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have found that triadica cochinchinensis tree contains Coumarinolignoids (coumarin), which has anti-inflammatory, antioxidant, and hepatoprotective effects. It also contains taraxeranes, which have cytotoxic and allelopathic effects (19). Qinpiting and ent-kaurane-3-oxo-16a, 17-diol in the stems and leaves of triadica cochinchinensis tree have a significant inhibitory effect on the release of NO from BV-2 microglia activated by LPS.…”
Section: Introductionmentioning
confidence: 99%